2021
DOI: 10.1155/2021/9983900
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in the Cornea: Insights from Other Tissues

Abstract: Extracellular vesicles (EVs) are phospholipid bilayer-bound particles secreted by cells that have been found to be important in mediating cell-cell communication, signal transduction, and extracellular matrix remodeling. Their role in both physiological and pathological processes has been established in different tissues throughout the human body. The human cornea functions as a transparent and refractive barrier that protects the intraocular elements from the external environment. Injury, infection, or diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 102 publications
0
26
0
Order By: Relevance
“…Following the isolation of HCK-, HCF-, and HCM-EVs, there are many normalization strategies varying between cell number, lipid concentration, or particle counts, but we kept a constant protein concentration, akin to previous corneal-related studies [ 11 , 16 , 41 ], as this eliminates any bias towards overdosing EV towards a different metric. Hence, the corneal stromal EVs used for the proteomic analysis and functional experiences were normalized by protein concentration and should reflect the differences in EV phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the isolation of HCK-, HCF-, and HCM-EVs, there are many normalization strategies varying between cell number, lipid concentration, or particle counts, but we kept a constant protein concentration, akin to previous corneal-related studies [ 11 , 16 , 41 ], as this eliminates any bias towards overdosing EV towards a different metric. Hence, the corneal stromal EVs used for the proteomic analysis and functional experiences were normalized by protein concentration and should reflect the differences in EV phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…To date, our understanding of stromal cells, such as adipocytes, fibrocytes, fibroblasts, and mesenchymal stem cells (MSCs), along with their secreted EVs, has been reported in studies that mediate disease-exacerbating changes in asthma [ 17 ], cancer [ 18 , 19 , 20 , 21 , 22 ], fibrosis [ 23 , 24 , 25 ], and cardiovascular diseases [ 26 , 27 , 28 ], but also show the therapeutic action of MSC-EVs by targeting different tissues, including the lungs, placenta, and thymus [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. By focusing on the cornea, studies have investigated how corneal MSC-EVs can improve corneal epithelial wound healing, reduce corneal epithelial defects, and promote scarless stromal recovery post-corneal injury in vivo [ 38 , 39 , 40 , 41 ]. These studies revealed a novel application of EVs as therapeutic carriers of cargo that promotes corneal tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Among these are bone-marrow-derived MSCs (BM-MSCs), whose potential therapeutic effects in CVDs were theoretically translated from their wide differentiation capacity [ 20 ]. Besides, recent studies revealed that MSCs reparative effects could occur through paracrine manner as well [ 21 , 22 , 23 , 24 , 25 ]. Being one of the best known sources of progenitor cells, BM-MSCs are successfully capable of differentiation into cardiomyocyte, and thus, several reports point to their importance as a reliable therapeutic approach for several CVDs [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, certain proteins, including classic exosomal markers, are present and may be used as exosomes markers following the minimum guidelines set by the International Society of Extracellular Vesicles (ISEV) [10]. An array of exosomes markers such as the tetraspanin proteins (CD9, CD63, and CD81), flotillin-1/-2, ESCRT-related (ALIX and TSG101), RABs, SNAREs, and others have been reported in different disease models [11][12][13][14][15][16][17][18]. However, with a particular focus on budding and infection of viruses, recent studies showed that nucleic acids, proteins, and even virions of enveloped viruses can be wrapped into the exosomes and transmitted between cells by the "free ride" of exosomes.…”
Section: Introductionmentioning
confidence: 99%